Evidence Based Clinical Study on Psoriasis (Advancements in Homeopathic Research, 2022)
500 well diagnosed cases of PSORIASIS were enrolled for treatment at Geetanjali Homoeopathic Clinic & Research Center, Lucknow from JANUARY 2009 to JANUARY 2017. Clinical diagnosis followed by constitutional treatment with homoeopathic medicines showed encouraging results in majority of the cases. Out of 500 cases 180 cases showed complete disappearance of all the silvery white scales from all parts of the body with absolutely no recurrence of any symptoms reported till date, while 220 cases showed much improvement in most of the patches with mild recurrence of the psoriatic patches and rest 54 cases did not show any response to the treatment. 46 cases worsened after treatment in which increment in size and number of Psoriatic patches were observed.
Keywords: dignois; cases; patches; report